(untitled) (International Journal of Medical and Surgical Sciences, 2016)
Osteochondroma of the scapula is a rare benign tumor in view of its location, which produces pain and mechanical dysfunction of the joint when it is on the ventral surface of the scapula, mainly affecting men during bone growth periods, between the ages of 10 and 30, accounting for 14.4 % of all scapula tumors and 49 % of benign tumors of the scapula. They arise in the metaphyseal regions of the long bones (femur, humerus, tibia), causing mechanical irritation leading to functional impotence, bursitis, and fracture of the scapula. Few cases in flat bones have been described. Diagnosis is made with physical, clinical and complementary examinations, and must be confirmed by prior histopathology biopsy. The surgical indication includes mechanical dysfunction of a joint or tendon in relation to the size of the lesion, sarcomatous change being the procedure of choice in open surgical excision. The case of an 11-year-old girl who was diagnosed with a subscapular osteochondroma after previous excisional biopsy, is described below.